PERLINDUNGAN KONSUMEN TERHADAP IKLAN YANG MENGANDUNG JANJI BELUM PASTI DALAM PERDAGANGAN ELEKTRONIK: STUDI TERHADAP IKLAN VITAMIN ANAK GENEROS: Consumer Protection Against Advertisements Containing Uncertain Promises in Electronic Commerce: A Study of Advertisements for Generos Children's Vitamins - Abigail Herlin Wibowo Putri; Sharda Abrianti (Faculty of Law, Universitas Trisakti, 2025)
There are still many advertisements displayed via electronic commerce in Indonesia that do not comply with the regulations relating to advertising. One of them is an advertisement for